PROFESSOR A. MAMAJONOV'S MASTERY IN USING UZBEK FOLK PROVER (Scientific journal of the Fergana State University, 2024)
This article presents the scientific and theoretical views of Professor A. Mamadjonov concerning linguistics. The scientist's monograph "Stylistics of complex sentence" will be analyzed. The work analyzes the use of proverbs using the rich and inexhaustible wealth of the folk language, syntactic and stylistic figures used in complex sentences - antithesis, anaphora, infora, parallelism, counting in complex sentences, ellipsis in complex sentences, inversion in conjunctions and their functions. The scientist's scientific views on stylistics, the ability to use folk proverbs, riddles and songs to reveal the stylistics of complex sentences will be covered.